2009
DOI: 10.1016/j.vaccine.2009.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of 23-valent pneumococcal polysaccharide vaccine in HIV-infected pregnant women and kinetics of passively acquired antibodies in young infants

Abstract: Whether gestational immunization of HIV-infected mothers with the 23-valent pneumococcal polysaccharide vaccine (PPV) confers maternal and infant early life, passive protection is not known. We evaluated safety, immunogenicity and placental transfer of antibodies in 44 HIV-infected women. Pneumococcal IgG antibodies against serotypes 1, 3, 5, 6B, 9V, and 14 were measured in mothers (pre-vaccination and at delivery), and infants (at birth, 1, 2, 3, and 6 months). PPV was safe and immunogenic in mothers. Newborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…The only study to estimate the time for the polysaccharide-specific antibody concentration to fall below the 0.35µg/mL correlate of protection was conducted in an HIV positive maternal population. This study reported geometric mean concentrations (GMC) above the threshold for a period of 0.6 months from birth for serotype 3 as compared to 2.0 and 2.7 months for serotype 5 and serotype 6B respectively [49].…”
Section: Maternal Vaccinationmentioning
confidence: 84%
“…The only study to estimate the time for the polysaccharide-specific antibody concentration to fall below the 0.35µg/mL correlate of protection was conducted in an HIV positive maternal population. This study reported geometric mean concentrations (GMC) above the threshold for a period of 0.6 months from birth for serotype 3 as compared to 2.0 and 2.7 months for serotype 5 and serotype 6B respectively [49].…”
Section: Maternal Vaccinationmentioning
confidence: 84%
“…In these studies, most pregnant women had not received pneumococcal vaccines, i.e., measured antibodies were induced by natural exposure to S. pneumoniae . However, while the transfer of naturally occurring (i.e., infection-induced) PCP IgG was reduced by about 20% in HIV-infected mothers (28, 35), antibody transfer ratios following immunization of pregnant women in Brazil with a pneumococcal polysaccharide vaccine was also reduced to only 46–72% as compared with unexposed newborns (36). Thus, infection-induced as well as vaccine-induced anti-PCP IgG transfer to her newborn is reduced in HIV-infected women.…”
Section: Impact Of Maternal Hiv Infection On the Transplacental Transmentioning
confidence: 99%
“…Moreover, PPV23 is safe and recommended for pregnant mothers. Newborns may receive 46–72% of maternal Ab titers from PPV23-vaccinated mothers, suggesting prolonged passive protection induced by maternal PPV23 vaccination [140, 141]. More effective vaccination strategies to elicit robust and sustained Ab responses against pneumococcal infection are needed for HIV-infected infants.…”
Section: Introductionmentioning
confidence: 99%